2010
DOI: 10.1152/ajpheart.00254.2009
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide RNA expression profiling in lung identifies distinct signatures in idiopathic pulmonary arterial hypertension and secondary pulmonary hypertension

Abstract: Idiopathic pulmonary arterial hypertension (PAH) is a life-threatening condition characterized by pulmonary arteriolar remodeling. This investigation aimed to identify genes involved specifically in the pathogenesis of PAH and not other forms of pulmonary hypertension (PH). Using genomewide microarray analysis, we generated the largest data set to date of RNA expression profiles from lung tissue specimens from 1) 18 PAH subjects and 2) 8 subjects with PH secondary to idiopathic pulmonary fibrosis (IPF) and 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 76 publications
5
163
0
Order By: Relevance
“…For the latter comparison, a two-gene intersection was identified (vaccinia related kinase 2, proteasome subunit, a type 3). Although there are no prior published studies that have explored microarray expression profiles of PH or elevated TRV in SCD, comparison of the 631 dysregulated genes for an elevated TRV to published dysregulated genes in patients with PAH revealed greater than 50 common genes (17). Such a large overlap of genes provides further evidence of the genes that have surfaced from the current study for an elevated TRV and their potential for predicting PH in SCD (Table E4).…”
Section: Functional Analysis Of Differentially Regulated Genes and Comentioning
confidence: 63%
“…For the latter comparison, a two-gene intersection was identified (vaccinia related kinase 2, proteasome subunit, a type 3). Although there are no prior published studies that have explored microarray expression profiles of PH or elevated TRV in SCD, comparison of the 631 dysregulated genes for an elevated TRV to published dysregulated genes in patients with PAH revealed greater than 50 common genes (17). Such a large overlap of genes provides further evidence of the genes that have surfaced from the current study for an elevated TRV and their potential for predicting PH in SCD (Table E4).…”
Section: Functional Analysis Of Differentially Regulated Genes and Comentioning
confidence: 63%
“…Recent genomic studies using surgical biopsies from patients with IPF support these findings, and have, in addition, demonstrated pathological gene expression changes in processes such as coagulation, angiogenesis, inflammation, apoptosis, and regeneration (11)(12)(13)(14)(15). These studies revealed a number of possible pathological pathways, and helped to identify candidate biomarkers that could be used for early diagnosis, prognosis, and disease progression monitoring (16)(17)(18)(19)(20).…”
Section: Clinical Relevancementioning
confidence: 82%
“…The impact of epigenetic changes such as DNA methylation and histone modification has been better documented in the pathogenesis of other human diseases [33][34][35][36], while the application of genomic technologies in human PAH samples are relatively limited. To date, except for a few studies [37][38][39][40], the approaches employed to delineate the disease mechanisms in PAH have not provided a global perspective of the molecular network underlying the disease phenotype. To gain insight into the mechanisms leading to the development of PAH, a broad range of high-throughput techniques in genomics, proteomics and metabolomics can be employed to systematically dissect the disease-specific networks in isolated pulmonary vascular cells, peripheral blood mononuclear cells and pulmonary tissues collected from patients.…”
Section: Discussionmentioning
confidence: 99%